Respostas
respondido por:
0
y=x²-3
3.x²=x²-3 (onde tiver y ponha 3.x²)
3.x² - x² + 3 =0
2.x² +3 = 0
x² = -3/2
x = √-3/2
y=-x²+2.x
3.x²+x²-2.x=0
4.x²-2.x=0
x.(4-2)=0 (põe o x em evidencia)
x'=2
x"=-4 espero ter ajudado avalie grato.
3.x²=x²-3 (onde tiver y ponha 3.x²)
3.x² - x² + 3 =0
2.x² +3 = 0
x² = -3/2
x = √-3/2
y=-x²+2.x
3.x²+x²-2.x=0
4.x²-2.x=0
x.(4-2)=0 (põe o x em evidencia)
x'=2
x"=-4 espero ter ajudado avalie grato.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás